2020 IEEE 31st Annual International Symposium on Personal, Indoor and Mobile Radio Communications 2020
DOI: 10.1109/pimrc48278.2020.9217368
|View full text |Cite
|
Sign up to set email alerts
|

A Tb/s Indoor Optical Wireless Backhaul System Using VCSEL Arrays

Abstract: In this paper, the design of a multiple-input multiple-output (MIMO) optical wireless communication (OWC) link based on vertical cavity surface emitting laser (VCSEL) arrays is systematically carried out with the aim to support data rates in excess of 1 Tb/s for the backhaul of sixth generation (6G) indoor wireless networks. The proposed design combines direct current optical orthogonal frequency division multiplexing (DCO-OFDM) and a spatial multiplexing MIMO architecture. For such an ultrahigh-speed line-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Progress in VCSEL technology has also led to many FSO sources that could be modulated independently on a single chip [119]. There are also various designs of photodetector arrays [120]. Newly developed photonic antennas can be incorporated to extend the field of view of high-speed optical detectors [121].…”
Section: Mimo Hybrid Rf/fsomentioning
confidence: 99%
“…Progress in VCSEL technology has also led to many FSO sources that could be modulated independently on a single chip [119]. There are also various designs of photodetector arrays [120]. Newly developed photonic antennas can be incorporated to extend the field of view of high-speed optical detectors [121].…”
Section: Mimo Hybrid Rf/fsomentioning
confidence: 99%
“…Depending on the bias current, the VCSEL output beam profile can be Gaussian Gaussian [20], [21], [22]. The geometrical representation of the Gaussian beam is shown in Fig.…”
Section: A Gaussian Beammentioning
confidence: 99%
“…For the bestcase scenario, it is assumed that all the beams are utilizing different wavelengths, which should be perfectly distinguished by the optical receiver. Therefore, the system is noise limited as ICI is completely avoided and the signal to interferenceplus-noise ratio (SINR) is represented as shown in (22). Hence, the average data rate of the central beam can be written as:…”
Section: B System With Multiple Usersmentioning
confidence: 99%
“…High-speed and high-brightness vertical-cavity surfaceemitting lasers (VCSELs) have plentiful applications nowadays. It has been suggested that such VCSEL arrays can be used as the light source in optical wireless communication (OWC) channels, one possible solution for development of the next generation of wireless communication systems for 5G, 6G and satellite communications [1,2]. A Space-Comm.…”
Section: Introductionmentioning
confidence: 99%